Conceptualising The Antecedents of eWOM in The Post-Consumption Behaviour Assessment of Tourism Sports Activities - Othman, Nuraimi; Rashid, Basri; Ramely, Asmahany (UUM Press, 2023)
Given the popularity of electronic media in today’s digital information era, visitors are likely to share their visit experience online with their colleagues or the public, especially on popular social media platforms. Thus, word-of-mouth practice has moved from physical word-of-mouth to online word of mouth, known as electronic word-of-mouth (eWOM). Responding to this new phenomenon, this paper attempts to propose a testable research framework for assessing tourism sports activities experience at the tourist destination. In other words, this paper aims to identify the antecedents of eWOM among tourism sports customers. Methodically, desk research was carried out whereby past literature was exhaustively reviewed to establish a conceptual understanding of tourism sport experience assessments and to consolidate the variables as a working model. In this context, this paper proposed a relational model that explains the effect of the perceived value, satisfaction, commitment and electronic media (e-media) familiarity on eWOM. This model also anticipated the moderation role of e-media familiarity between commitment and eWOM. Theoretically, the proposed framework reduces the gaps related to the construction of research variables for tourism sports experience assessment. Practically, this paper provides sport tourism operators with a comprehensive testable framework that can guide them in understanding their customers’ consumption behaviour assessment process and their electronic word-of-mouth response.